Hubungan Spiritualitas dengan Persepsi Sakit Masyarakat Petani di Desa Tamanarum, Magetan - Rakasiwi, Sabella; Ardiana, Anisah; Nur, Kholid Rosyidi Muhammad; Purwandari, Retno; Afandi, Alfid Tri (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Farmers are vulnerable to heavy physical work, pesticides used, and climate change, which are risks of health problems. The farmers' perception of the symptoms of the disease that appear will influence the management of the health problems they experience. This perception is influenced by spirituality as part of the farmer's support system in living his life as a human being who is also a spiritual being. This study aims to find out how the relationship between spirituality and the perception of illness in the farmer community in Tamanarum Village, Magetan. The study used a cross-sectional approach with a cluster random sampling technique. The respondents were 367 people who met the inclusion criteria. Data were collected through illness perception questionnaires and the Daily Spiritual Experience Scale (DSES). Data were analyzed univariate and bivariate with the Kendall Tau test Î±= 0.05. The majority of farmer communities had high spirituality, with 336 respondents (91%), and 329 respondents (89.6%) having a positive perception of illness, and there is a relationship between spirituality and perception. It can be concluded that many factors influence the perception of illness, and spirituality plays a role in individual understanding, which is closely related to responding to symptoms of illness.